Two new species of the acifer species group of Polypedilum subgenus Tripodura Townes from China (Diptera: Chironomidae) - Zhang, Ruilei; Song, Chao; Wang, Liqing; Wang, Xinhua (Zootaxa, 2015)
Polypedilum (Tripodura) falcatum sp. n. and P. (T.) procerum sp. n. of the acifer species group of Polypedilum subgenus Tripodura Townes are described and illustrated as male imagines from China. The male adult of P. (T.) falcatum sp. n. is distinguished by the presence of two faint markings on wing; short and interrupted abdominal tergite bands; the sickle-like superior volsella bearing 0–2 outer setae and a tuft of short setae on its apex. The male adult of P. (T.) procerum sp. n. differs in having short abdominal tergite bands; a long, slender and apically curved superior volsella; a high fore leg ratio (2.30–2.33). A key to known male imagines of Polypedilum subgenus Tripodura from China is presented.